Amyloid structures: much more than just a cross-β fold. (February 2020) - Gallardo, Rodrigo; Ranson, Neil A; Radford, Sheena E
Highlights: New structures have shown that there is a remarkable diversity and complexity of the amyloid fold. The same sequence forms different amyloid structures in different diseases. Polymorph selection in vivo is likely dependent on cellular and extracellular constraints. Locally disordered regions in amyloid fibrils are functionally and structurally important. Ligand binding, post-translational modifications and non-protein components contribute to the structural diversity of the amyloid fold. Graphical abstract: Solving the amyloid puzzle requires an integrated use of structural and functional approaches. Abstract : In recent years our understanding of amyloid structure has been revolutionised by innovations in cryo-electron microscopy, electron diffraction and solid-state NMR. These techniques have yielded high-resolution structures of fibrils isolated from patients with neurodegenerative disease, as well as those formed from amyloidogenic proteins in vitro . The results not only show the expected cross-β amyloid structure, but also reveal that the amyloid fold is unexpectedly diverse and complex. Here, we discuss this diversity, highlighting dynamic regions, ligand binding motifs, cavities, non-protein components, and structural polymorphism. Collectively, these variations combine to allow the generic amyloid fold to be realised in three dimensions in different ways, and this diversity may be related to the roles of fibrils in disease.